Sterile Postbiotic Supernatants from Lactic Acid Bacteria Reduce LPS-Induced Inflammatory and Oxidative Stress Markers in Mammalian Epithelial Cells Without Direct Bacterial Contact - Dagman, Sabreen Noori (American Journal of Biology and Natural Sciences, 2026)
Background: Postbiotics are non-viable microbial products or metabolites that may regulate mammalian epithelial responses without the biosafety concerns linked with live bacteria. Their effects can be studied using commercial mammalian cell lines without animals, human samples, histology, microscopy, or gel electrophoresis. Aim: This study evaluated whether sterile cell-free supernatants from lactic acid bacteria could reduce inflammatory and oxidative stress responses in mammalian epithelial cells exposed to lipopolysaccharide. Methods: Commercial mammalian epithelial cells were cultured in four groups: untreated control, lipopolysaccharide-stimulated control, lipopolysaccharide plus Lactiplantibacillus plantarum cell-free supernatant, and lipopolysaccharide plus Lacticaseibacillus rhamnosus cell-free supernatant. Supernatants were filtered through 0.22 µm filters, neutralized to pH 7.0, and tested at non-cytotoxic concentrations. Cell viability, nitric oxide, malondialdehyde, glutathione, interleukin-6, interleukin-8, and selected inflammatory gene-expression markers were measured using plate-reader assays, ELISA, and RT-qPCR with melt-curve confirmation. Results: Lipopolysaccharide increased IL-6 from 41.6 ± 4.8 to 192.4 ± 15.7 pg/mL and IL-8 from 78.5 ± 7.6 to 346.2 ± 24.1 pg/mL. Treatment with L. plantarum supernatant reduced IL-6 to 96.8 ± 9.3 pg/mL and IL-8 to 181.7 ± 16.4 pg/mL. L. rhamnosus supernatant reduced IL-6 to 113.5 ± 10.1 pg/mL and IL-8 to 209.4 ± 18.6 pg/mL. Malondialdehyde and nitric oxide were also significantly decreased, while glutathione and cell viability were improved. RT-qPCR showed downregulation of TLR4, NFKB1, IL6, and CXCL8 expression in postbiotic-treated groups. Conclusion: Sterile lactic acid bacterial supernatants reduced inflammatory and oxidative stress responses in mammalian epithelial cells without direct bacterial contact. This model provides a simple microbiology–mammalian interface study suitable for publication without animals, human samples, gel electrophoresis, histology, or image-based verification.